2020
DOI: 10.1038/s41598-020-60135-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and metabolome responses in the cecum and serum of broiler chickens fed with plant essential oils or virginiamycin

Abstract: This study investigated the cecal microbiota and serum metabolite profile of chickens fed with plant essential oils (PEO) or virginiamycin (VIRG) using high-throughput 16S rRNA gene sequencing and untargeted metabolomics approach. the main aim of this work was to explore the biochemical mechanisms involved in the improved growth performance of antibiotics and their alternatives in animal production. The results showed that both PEO and VIRG treatment significantly increased the relative abundance of phyla Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 71 publications
9
43
0
Order By: Relevance
“…This negative correlation may be due to the fact that Bacteroides are generally related to polysaccharide degradation, especially of starch and glucans ( Degnan et al., 1997 ; Beckmann et al., 2006 ). Bacteroides are also linked to SCFA formation and positively correlated with many lipid metabolites ( Saxena et al., 2016 ; Chen et al., 2020 ). These characteristics may favor the improvement of host FE.…”
Section: Discussionmentioning
confidence: 99%
“…This negative correlation may be due to the fact that Bacteroides are generally related to polysaccharide degradation, especially of starch and glucans ( Degnan et al., 1997 ; Beckmann et al., 2006 ). Bacteroides are also linked to SCFA formation and positively correlated with many lipid metabolites ( Saxena et al., 2016 ; Chen et al., 2020 ). These characteristics may favor the improvement of host FE.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli have been shown to be negatively correlated with lipid metabolism. They accelerate the synthesis of lipid peroxidation metabolites and are positively related to intestinal health (Chen et al, 2020). Some experiments related to the addition of Lactobacilli also revealed that they have the potential to improve the performance, digestion, and feed utilization efficiency of broilers and laying hens (Saleh et al, 2017(Saleh et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the administration of a commercial EO mixture, containing cinnamaldehyde, isophorone and eugenol significantly increased the relative abundance of phyla Bacteroidetes and decreased the abundance of phyla Firmicutes in cecal microbiota of chickens, with an increase in the relative abundance of genus of Alistipes, Rikenellaceae, Roseburia, and Anaeroplasma. This microbioma changes was confirmed by more than hundred different metabolites detected in cecum of EO treated animals, probably linked to their improved growth performances [141,142].…”
Section: Eubiotic Proprieties Of Eos On Gut Microbiota Of Animals Andmentioning
confidence: 66%
“…Similar results were obtained in a rat model of type 2 diabetes, in which G. lucidum treatment reduced the relative abundance of harmful bacteria, such as Aerococcus, Ruminococcus, Corynebacterium and Proteus, and increased the levels of Blautia, Dehalobacterium, Parabacteroides and Bacteroides. Microbiome analysis indicated that Reishi treatment could also restore the microbial metabolism of amino acids, carbohydrates, inflammatory substances and nucleic acids, altered by the obesity status [141,142]. Taken together, these results indicate that G. lucidum and particularly its high molecular weight polysaccharides may be effectively used as prebiotic agents to prevent gut dysbiosis and obesity-related metabolic disorders, at least in obese rodents.…”
Section: Microbiota-modulating Fungimentioning
confidence: 82%